Análisis de la demanda turística para la creación de cabañas en la Playita el Salto - Lozano Arbelaiz, Merly Dayanna (2021)
The development of this work is oriented in the analysis of the tourist demand for the creation of cabins in the beach of El Salto, an urban parish of the Babahoyo canton in the province of Los Ríos. Its purpose is to analyze the demand around the implementation of cabins on said beach, and how feasible they would be in this area, given the lack of knowledge of the population about the opportunities offered by a transcendental tourist culture. To carry out the work of compiling information on the analysis of tourist demand for the creation of cabins on the beach of El Salto, the qualitative and quantitative method was taken into consideration, directing to exploratory, descriptive, documentary and social research, basing their assertions through online surveys, observation and data tabulation. These revised data will allow to identify how to calculate the demand for a tourist attraction in development, quite apart from providing all the tools to know how all this study should be applied before the implementation of a new infrastructure within a natural or cultural tourist space, all this planning must be professional and the methods to be applied must be reliable. The demand analysis also provides the opportunity to not only be directed to calculate the influx of tourists that may reach a destination, but also provides important data on the part of the tourist such as behavioral, preferential and needs. Providing the macro analysis that would contribute to the management of the project and its sustainability over time through the indicators presented in the study.